2021
DOI: 10.3389/fimmu.2021.690234
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Alpha-Ketoglutarate Supplementation on the Improvement of Intestinal Antioxidant Capacity and Immune Response in Songpu Mirror Carp (Cyprinus carpio) After Infection With Aeromonas hydrophila

Abstract: As an intermediate substance of the tricarboxylic acid cycle and a precursor substance of glutamic acid synthesis, the effect of alpha-ketoglutarate on growth and protein synthesis has been extensively studied. However, its prevention and treatment of pathogenic bacteria and its mechanism have not yet been noticed. To evaluate the effects of alpha-ketoglutarate on intestinal antioxidant capacity and immune response of Songpu mirror carp, a total of 360 fish with an average initial weight of 6.54 ± 0.08 g were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 78 publications
1
17
0
Order By: Relevance
“…Based on the strength of the second-order polynomial regression analysis of WGR and FCR, the requirement of dietary lipids for large-sized common carp with an IBW of 247.00 ± 16.67 g was estimated to be 59.5-70.4 g/kg. This requirement is 10-30 g/kg lower than that observed in common carp with an IBW of 5.51 ± 0.05 g (24), common carp with an IBW of 15 g (26), and common carp with an IBW of 36.12 ± 1.18 g (5). The above difference supports somehow the hypothesis that there is a more excellent nutritional requirement in the juvenile stage.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Based on the strength of the second-order polynomial regression analysis of WGR and FCR, the requirement of dietary lipids for large-sized common carp with an IBW of 247.00 ± 16.67 g was estimated to be 59.5-70.4 g/kg. This requirement is 10-30 g/kg lower than that observed in common carp with an IBW of 5.51 ± 0.05 g (24), common carp with an IBW of 15 g (26), and common carp with an IBW of 36.12 ± 1.18 g (5). The above difference supports somehow the hypothesis that there is a more excellent nutritional requirement in the juvenile stage.…”
Section: Discussionsupporting
confidence: 69%
“…The common carp production in 2018 was 2,962,218 tons in China, which ranked at the fourth position out of a total of 25 species evaluated (23). However, to our knowledge, the available information on the dietary lipid requirement for common carp was limited to juvenile common carp with the body weights below 20 g and on growing common carp with the weights ranging from 20 to 100 g (24). Xu et al (24) obtained the results from the study on common carp [an initial body weight (IBW) of 5.51 ± 0.05 g] in which the optimum dietary lipid requirement of juvenile common carp was 8% at 16 • C and 11% at 23 • C in terms of immunity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study has shown that AKG played a critical role in the intestinal immunity, and AKG could significantly increase the thickness of intestinal muscle layer and fold height and significantly enhance the activities of intestinal digestive enzymes ( 19 ). In addition, it has been confirmed that AKG alleviated the decline in intestinal function caused by the inflammatory response after Aeromonas hydrophila infection ( 20 ). However, the mechanism by which AKG regulates the immune function and structural integrity of the intestine health in an LP diet remains unclear in fish.…”
Section: Introductionmentioning
confidence: 91%
“…Considering that little evidence addressed the effect of Thr on immunocyte activation, it still needs further investigation. Once awakened by antigens in an immunologic process, innate immune factors produced by immunocytes, like LZ and C3 derived by macrophages, ACP released by leukocytes simultaneously executed the defense role by breaking down the foreign antigens in the immune organs of fish (86). In our study, compared with the Thr-insufficient-diet group, the optimal Thr level enhanced the enzyme activity of LZ and ACP, complement contents (C3 and C4), and gene expression of antimicrobial compounds hepcidin, LEAP-2A, LEAP-2B, and b-defensin1 in the HK and SP of juvenile grass carp after the challenge with A. hydrophila.…”
Section: Thr Improved the Immune Status And Mediated The Inflammation...mentioning
confidence: 99%